2008
DOI: 10.1136/jramc-154-01-08
|View full text |Cite
|
Sign up to set email alerts
|

Why Military Personnel Fail to Keep Medical Appointments

Abstract: The most common reasons for not attending appointments were due to administrative error and an inability amongst patients to recall the correct date of the appointment. Whilst efforts to improve attendance through various reminder systems have been found to be effective in the short term at least, improvements in the efficiency of appointment administration is likely to generate a reduction in DNA and in turn will reduce the wastage of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Similar reasons were reported in a general practice in the United Kingdom 6 and a military clinic in the United States. 15 The miscommunication category included patients who said they thought they had canceled the appointment, patients who thought the appointment was a different date or time, patients who tried to call the clinic but did not get through, and patients who did not realize they needed to call and cancel.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reasons were reported in a general practice in the United Kingdom 6 and a military clinic in the United States. 15 The miscommunication category included patients who said they thought they had canceled the appointment, patients who thought the appointment was a different date or time, patients who tried to call the clinic but did not get through, and patients who did not realize they needed to call and cancel.…”
Section: Discussionmentioning
confidence: 99%
“…Time off duty will be available on more cases and also more accurate when these figures are collected prospectively. The limited data available on quality of care suggest that all patients were seen promptly at BHH and that only 5% failed to attend compared to 10% in a previous study of military out-patients [7]. However, improvements could be made in communication with patients' own medical officers and military public health staff.…”
Section: Discussionmentioning
confidence: 90%
“…64 Other studies investigating military personnel have found the most frequently reported reason for missing appointments was administrative error (including believing their appointment was on another date, having cancelled the appointment, and not knowing they had an appointment). 65 Furthermore, due to limitations of this archival collection, demographics (e.g., gender differences 15,51 ) and other individual barriers to care (e.g., distance from the facility and/or finances 66 ) were not able to be assessed. Future studies would benefit from controlling for these variables to better understand the unique contribution of weather on treatment compliance for those with chronic pain conditions.…”
Section: Discussionmentioning
confidence: 99%